Habitação de interesse social: avaliação de pós ocupação em residencial no município de Guarabira/PB - Fernandes, André Luis Coelho (2023)
Urban challenges are complex and difficult to address by the government. Among them, the housing deficit for low-income individuals stands out as one of the most relevant issues. Social Interest Housing, the central theme of this study, proposes adopting a contemporary perspective on habitability as a new concept of housing, the surrounding environment, and the peculiarities of the beneficiaries selected for occupancy. The main objective of this research is to evaluate the post-occupancy of the Jáder Soares Pimentel Residential, with the purpose of improving the actions and social interest housing policy of the Municipal Government of Guarabira/PB. To achieve this, a bibliographic and documentary research was conducted to explore national and international literature, as well as access the laws and documents related to the studied project. In order to achieve triangulation that would provide greater methodological rigor and immersion in the field, data collection was carried out through three data collection instruments: questionnaire (residents), focus group interview script (housing team), and field observation script (on-site visits). Both quantitative and qualitative approaches were adopted, depending on the nature of the data. The quantitative data (242 respondents) were subjected to multivariate analysis, while the qualitative data were subjected to content analysis. The items with the highest ratings were identified as follows: health center; ventilation and direct lighting in the rooms of the apartments; community facilities adapted for people with disabilities and/or reduced mobility; low level of urban violence; awareness of government actions; waste collection; satisfaction with the electrical grid; and pedestrian access. The lowest ratings were given to the following items: sports court; police station; social assistance center; access to childcare; opportunities for youth to engage in sports, leisure, and cultural activities; residents' participation in the maintenance of facilities; and social participation and interaction groups. For group comparisons, Analysis of Variance and Student's t-test were used, with correction procedures (bootstrapping). Significant differences between certain groups were identified through these comparisons. Based on the findings, suggestions for improving the municipality's public housing policy and the subsequent stages of the Residential Complex were presented.